From Speech to Song: A Response to Johnson, Huron and Collister on the Interaction of Music and Lyrics - Wickham, Edward (Empirical Musicology Review, 2013)
This commentary addresses some of the methodological difficulties inherent in studying intelligibility in sung text. It provides observations which complement and critique some of the authors’ hypotheses and conclusions, and offers a caveat to further ‘bottom-up’ studies of text intelligibility in music.